If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 3) + -4 = 16 Reorder the terms: 5(3 + x) + -4 = 16 (3 * 5 + x * 5) + -4 = 16 (15 + 5x) + -4 = 16 Reorder the terms: 15 + -4 + 5x = 16 Combine like terms: 15 + -4 = 11 11 + 5x = 16 Solving 11 + 5x = 16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 5x = 16 + -11 Combine like terms: 11 + -11 = 0 0 + 5x = 16 + -11 5x = 16 + -11 Combine like terms: 16 + -11 = 5 5x = 5 Divide each side by '5'. x = 1 Simplifying x = 1
| 2(2-3x)=4(1-3/2) | | n-3=0.7 | | 3x^3-20x^2+43x-30=0 | | 9-1.3x=1.3x-9 | | 4n-6+1-8n= | | -6x+10=-4x+-16 | | (7+x)(6+x^2)=55 | | p-2+6=p | | y-5=(6/5)(x-6) | | p+6=p-2 | | 180=35+5x | | 2x+4=-2x+-12 | | -14(y)= | | 2a-6=24 | | 180=13x+38 | | 3x+2x=12+18 | | 180=38+13x | | 2t+9+3t+1=5t+8t-10 | | y=7+8x | | -196=14d+30 | | 3+3x=9x+6 | | 6x+6x+3x+49=96x+3x+x | | 14k+8k+88=163 | | 25=4a+19 | | y=x2−2x+48x+y=20 | | 0.04(4c-80)=-0.8(C-2) | | 2x+10-x=2(2x-6) | | 13-x=x^2+1 | | 73=0.7-4 | | 32=4a+19 | | 8(s-92)=32 | | 4(2)+3(-3)=-1 |